Ambidexterity Leadership Behaviors and Their Impact on Organizational Immunity in the Iraqi Ministry of Education - abass, donia; Abdul Qader Al-Naimi , Salah (Journal of Economics and Administrative Sciences, 2025)
This study investigates the effect of ambidextrous leadership behaviors on organizational immunity in the Iraqi Ministry of Education. Based on ambidextrous leadership theory which is a balance between open and closed leadership behaviors, the study investigates how these two dimensions impact organizational learning, memory, and DNA. Using a descriptive-analytical approach, data was collected through questionnaires and interviews from 183 administrative leaders. The results indicate that organizational immunity is significantly affected by open leadership behaviors as well as closed leadership behaviors. Open behaviors foster innovation, knowledge sharing, and collaborative problem solving, whereas closed behaviors maintain structure, consistency, and focus on goal achievement. Further, ambidextrous leadership allows the ministry to strengthen its resilience and perform proactive decision-making in the face of internal and external challenges. Reliable information, employee engagement, and strategic planning have been highlighted as some of the key factors by the study in building a strong organizational immune system. The results suggest that investing in leadership development can enhance adaptability and long-term stability in public institutions.